2022
DOI: 10.1038/s41398-022-01911-3
|View full text |Cite
|
Sign up to set email alerts
|

Depressive disorders are associated with increased peripheral blood cell deformability: a cross-sectional case-control study (Mood-Morph)

Abstract: Pathophysiological landmarks of depressive disorders are chronic low-grade inflammation and elevated glucocorticoid output. Both can potentially interfere with cytoskeleton organization, cell membrane bending and cell function, suggesting altered cell morpho-rheological properties like cell deformability and other cell mechanical features in depressive disorders. We performed a cross-sectional case-control study using the image-based morpho-rheological characterization of unmanipulated blood samples facilitati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…Consistent with our previous observation, major depressive patients exhibit signi cantly lower percentage of CD45 + lymphocytes and elevated CD4 + CD8 − -CD3 + T cells with decreased CD4 − CD8 + -CD3 + T cells (Yang, Ning, et al 2020). A recent paper reported depressive disorders were associated with increased peripheral blood cell deformability (Walther et al 2022). Moreover, a largest transcriptome-wide association study (TWAS) for postpartum depression con rmed that B cells had a majority of transcriptome-wide signi cant changes, implicating altered B-cell activation and insulin resistance (Walther et al 2022).…”
Section: Expression Pattern Of Probdnf/p75ntr In Peripheral Immune Cellssupporting
confidence: 90%
“…Consistent with our previous observation, major depressive patients exhibit signi cantly lower percentage of CD45 + lymphocytes and elevated CD4 + CD8 − -CD3 + T cells with decreased CD4 − CD8 + -CD3 + T cells (Yang, Ning, et al 2020). A recent paper reported depressive disorders were associated with increased peripheral blood cell deformability (Walther et al 2022). Moreover, a largest transcriptome-wide association study (TWAS) for postpartum depression con rmed that B cells had a majority of transcriptome-wide signi cant changes, implicating altered B-cell activation and insulin resistance (Walther et al 2022).…”
Section: Expression Pattern Of Probdnf/p75ntr In Peripheral Immune Cellssupporting
confidence: 90%
“…This observational study used a longitudinal design with a baseline measurement and a one-year follow-up measurement. Cross-sectional results of the study were reported elsewhere (Walther et al, 2022b). Baseline examination of participants took place between October and December 2018, while follow-up examinations were conducted one year later.…”
Section: Methodsmentioning
confidence: 99%
“…Only recently, using RT-DC, we were able to show that in DD and especially in PDD immune cell deformability is increased as compared to healthy controls (Walther et al, 2022b). Although all major blood cells tended to be more deformable, lymphocytes, monocytes and neutrophils were particularly affected indicating immune cell mechanical changes to occur in DD.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations